The Application of Playing Mathematics During the Covid-19 Pandemic to Stimulate Child Development at PAUD TPQ Jami'atul Imam Wonosobo - Fuad Khoirul Afif; Imam Mawardi (Konsorsium LPPM Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
This research is motivated by the low number of students at POS PAUD TPQ Jami'atul Imam in recognizing early mathematical concepts. This study aims to identify early childhood mathematical concepts through playing at home for the 4-5 year age group (TK A group) at POS PAUD TPQ Jami'atul Imam Academic Year 2021/2022. The method used in this research is classroom action research (CAR) with Kurt Lewin's model. This research consists of pre cycle, cycle I, cycle II. Cycles I and II consist of 4 stages, namely planning, implementation, observation, reflection. This data collection technique is in the form of video documentation. The results of this study are as follows: 1) Based on the results of data analysis and elaboration of the discussion about classroom action research, it can be concluded as follows: 1) Children are familiar with mathematical concepts from the start. 2) Children are brave and enthusiastic in carrying out the activities presented. 3) Children learn mathematics naturally by playing.